O repasse cambial para a inflação: análise empírica para os países da América Latina de 2000 a 2015 - Canabarro, Aline Teixeira (Universidade do Vale do Rio dos Sinos, 2017)
This dissertation aims to investigate which was the exchange retrace to the inflaction (pass-through), for the selected countries in Latin America, specially Brazil, Chile, Colombia and Mexico, under the macroeconomical focus, among the years 2000 and 2015. For such, it was used the VAR/VEC model. The results of the impulse-response functions (short time relation) indicate that for Brazil and Colombia, the Exchange rate pressures the increase of the inflaction and the pass-through is higher. While in Chile and Mexico the Exchange variations do not predominate the inflaction variations (endogeny movement), sendo o pass-through menor. Colombia presentes more sensibility to the exchange changes, followed by Brazil, Chile and Mexico, respectively. The long term equations show that in Brazil, Chile and Maxico the increase in the industrial production has the effect of reducing the inflaction of the country. It probably happens because of the scale effect generated in the production of these countries. Another result that is highlighted in the long term is that the exchange rate is not relevant in Brasil and Chile, suggesting that the changes in the Exchange rate do not have affect on the long term inflaction. The results point to similar directions of other studies, beyond the pass‑through degree being incomplete (assimetry) and the higher retrace be in countries with productive sectors of goods of lower technological content.
Keywords: América latina; Inflação; Modelo VAR/VEC; Pass-through; Taxa de câmbio; ACCNPQ::Ciências Sociais Aplicadas::Economia